Gendered Terrains: A Mixed-Methods Analysis of Lineage, Law, and Women's Land Inheritance in Indonesia's Batak and Minangkabau Communities - Fitriyanti Fitriyanti; Susi Diana; Yuniarti Maretha Pasaribu; Muhammad Hasan (Enigma Institute, 2025)
In Indonesia, the pluralistic legal landscape, where state, religious, and customary laws intersect, creates profoundly different realities for women's land rights. This study investigates the disparity between de jure principles and de facto outcomes in two of Indonesia's most prominent and contrasting customary systems: the patrilineal Batak Toba and the matrilineal Minangkabau. We employed a sequential explanatory mixed-methods design. The quantitative phase involved a multi-stage random survey of 400 households (200 Batak, 200 Minangkabau) to establish inheritance patterns. Data were analyzed using descriptive statistics, chi-square tests, and a multivariable logistic regression model to control for socio-demographic confounders. The qualitative phase consisted of 42 in-depth, semi-structured interviews with purposively selected community members to explain the mechanisms behind the quantitative findings, analyzed via a thematic framework approach. Quantitative findings reveal that 88% of Minangkabau women had inherited land compared to only 32% of Batak women. After controlling for age, education, and occupation, logistic regression showed that Minangkabau women had over 14 times the odds of inheriting land compared to Batak women (OR=14.72; 95% CI [7.15, 30.31], p< 0.001). Qualitative data revealed two divergent mechanisms producing these outcomes: 'Institutionalized Security' in the Minangkabau system, where rights are embedded in matrilineal identity, and 'Negotiated Permeability' in the Batak system, where access is contingent upon discretionary grants (hibah) from male relatives and is a major source of conflict. In conclusion, the structure of customary lineage remains the single most powerful determinant of women's land inheritance, an effect that state law has not superseded. While the matrilineal system provides institutionalized security, the patrilineal system renders women's rights precarious and conflict-prone. Advancing gender equity in land tenure requires engagement with the internal logic and adaptive capacities of these deeply entrenched customary orders.